Kewajiban Penyegeraan Pendaftaran Haji: Kajian Fatwa Majelis Ulama Indonesia Nomor 5 Tahun 2020 - Tarmizi M. Jakfar; Muji Mulia; Yusrizal Yusrizal (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
Based on information from Susenas 2017, there are about 13 million Indonesian Muslims who are already economically well-off for the hajj list, but do not register for the hajj. In response to this, MUI has issued a fatwa for people aged 60 to register immediately, worried about running out of fees and making up hajj and MUI stipulates that it is forbidden for them to delay. The research questions are: how is MUI's consideration in determining the obligation to immediately register for hajj for those who meet the criteria and how is MUI's consideration in determining the prohibition of delaying for those who meet the criteria. This research is classified as a type of qualitative research and is included in the normative study and the process of collecting data using the literature method is then analyzed with a descriptive analysis approach. The results found are that it is mandatory for people aged 60 years to register for Hajj immediately because of the hadith that states the average age of the Prophet Muhammad's people is 60-70 years, while the waiting period for departure is very long, for people who are worried about running out of money because it is analogous to the obligation to leave on Friday. at, and for qada hajj because there is a consensus of friends. As for the consideration of the prohibition of postponing the age of 60 because it is a sin to neglect worship, for people who are worried about running out of hajj fees because they violate the law from the results of analogies and for those who make up qada because they consider the consensus of friends.